2022
DOI: 10.33084/bjop.v5i4.3511
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of 96% Ethanol Extract of Pepaya Jepang Leaves (Cnidoscolus aconitifolius (Mill.) I. M. Johnst) Using DPPH Method (1,1-diphenyl-2-picrylhydrazyl)

Abstract: Free radicals in the human body can be helped neutralized by natural antioxidants derived from plants. Pepaya Jepang (Cnidoscolus aconitifolius (Mill.) I.M.Johnst) contains antioxidant compounds such as flavonoids and polyphenols. This study examined the antioxidant activity of 96% ethanol extract of C. aconitifolius leaves. Maceration of C. aconitifolius leaves using 96% ethanol solvent, phytochemical screening, and antioxidant activity assay was carried out with 1,1-Diphenyl-2-Picryl Hydrazil (DPPH) on 96% e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A previous study reported that 96% ethanol was used to extract various bioactive compounds, including alkaloids and polyphenol compounds, such as flavonoids and tannin. 22 A previous study also reported that different ethanol concentrations have been widely used in bioactive compound extraction. 23 Ethanol, or mixture of ethanol and water, is widely used as a solvent due to its safety and it is also categorized as a food-grade solvent.…”
Section: Extraction Yield and Phytochemical Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that 96% ethanol was used to extract various bioactive compounds, including alkaloids and polyphenol compounds, such as flavonoids and tannin. 22 A previous study also reported that different ethanol concentrations have been widely used in bioactive compound extraction. 23 Ethanol, or mixture of ethanol and water, is widely used as a solvent due to its safety and it is also categorized as a food-grade solvent.…”
Section: Extraction Yield and Phytochemical Compositionsmentioning
confidence: 99%
“…21 Additionally, a 96% ethanol solvent was also used to extract bioactive compounds from Cnidoscolus aconitifolius leaf. 22 According to the qualitative phytochemical analysis, this extract contains alkaloids, flavonoids, and tannins (Table 1). A previous study reported that 96% ethanol was used to extract various bioactive compounds, including alkaloids and polyphenol compounds, such as flavonoids and tannin.…”
Section: Extraction Yield and Phytochemical Compositionsmentioning
confidence: 99%
“…Antioxidant activity determined by DPPH assay of P. americana seeds maceration and reflux method refers to the procedure 23 with some modifications. 24 Preparation of a standard solution by weighing 5 mg of vitamin C dissolved in 50 mL of 96% ethanol to obtain a concentration of 100 ppm. Formulation of standard vitamin C curves with series concentrations of 2, 4, 6, 8, 10 µg/mL.…”
Section: Antioxidant Activitymentioning
confidence: 99%